Ecologic constituent of risk of reproductive complications - Golovkova, T. A. (Journal of Education, Health and Sport, 2018)
Technogenic pressure contributes to the constant emission of significant amounts of chemical pollutants in the environment, thus increasing the risk of ecologically conditioned pathology in the population of urbanized areas. Of the variety of environmental factors that have a detrimental effect on the body of a future mother, cadmium plays a particularly important role as a risk factor for complications in the course of pregnancy. Therefore, the purpose of the research was to determine the influence of external exposures of cadmium on the level of internal contamination of the body of pregnant women and the frequency of manifestation of nephropathy among residents of Dnipropetrovsk region in the complex impact of different levels of environmental pollution. The research program included an assessment of the cadmium content in life-saving environmental facilities and biological substrates of 89 healthy pregnant women, as well as a retrospective analysis of data of the primary statistical documentation on the complication of pregnancy. It is established that cadmium has a constant presence in environmental objects, in concentrations that do not exceed the normative meanings. The level of cadmium in the blood and urine of women in industrial districts is significantly higher in comparison with the control (p <0.01), up to 36-50% of Dnipro citizens have an increased cadmium content in urine relative to norm, and its concentrations have a direct correlation dependence with the frequency of manifestations of nephropathy of pregnant women in apparently women. The established enhanced renal excretion of cadmium reflects the stresses of adaptation processes in the body of the pregnant woman, which is possibly due to an increase in the toxic effect of xenobiotics in this vulnerable to the physiological state period.